Reference Intervals of Central Aortic Blood Pressure and Augmentation Index Assessed with an Oscillometric Device in Healthy Children, Adolescents, and Young Adults from Argentina - Alejandro Diaz; Yanina Zócalo; Daniel Bia; Edmundo Cabrera Fischer (International Journal of Hypertension)
Age-related reference intervals (RIs) of central (aortic) systolic blood pressure (cSBP) and augmentation index (cAIx) obtained from large healthy population are lacking in Argentina (South America). Aims. To analyze the existence of associations among cSBP and cAIx with demographic, anthropometric, and hemodynamic parameters and to generate percentile curves and RIs adjusted to each level of age and gender and/or body height. cSBP and cAIx were measured in 1038 healthy children, adolescents, and young adults. First, we evaluated if RIs for males and females were necessary using correlation and covariate analysis. Second, mean (M) and standard deviation (SD) age-related equations were obtained for cSBP and cAIx, using parametric regression methods based on fractional polynomials. Third, age specific percentiles curves were generated. Fourth, body height specific percentiles curves were generated using a similar procedure. The obtained equations (considering age as independent variable) for all subjects (cSBP0.26 and (cAIx + 12.001)0.5) were as follows: cSBP Mean = 3.0581 + 0.2189 log(Age) − 0.001044Age; cSBP SD = −0.03919 + 0.1535 log(Age) − 0.004564Age; cAIx mean = 9.5226 − 6.1599 log(Age) + 0.1450Age; cAIx SD = 1.3880 − 0.8468 log(Age) + 0.03212Age. This study, performed in Argentinean healthy children, adolescents, and young adults with ages of 5 to 22 years, provides the first RIs and percentile curves of cSBP and cAIx. Additionally, specific body height-related cAIx percentiles are reported for the analyzed population. The RIs and percentiles contribute to the knowledge of arterial dynamic evolution along the normal aging process and the interpretation of data obtained in clinical research and daily clinical practice.